AI in Environmental Sustainability: A Review of Applications and Challenges - Choudhary, Abhilasha; Sharma, Sulochana; Singh, Ranveer; Choudhary, Abhishikha (Journal of Multidisciplinary Research Advancements, 2025)
The paper explores the major effects of Artificial Intelligence (AI) in promoting sustainable development in Indian context. It covers its expanding impact in important sectors such as agriculture healthcare, renewable energy resources, education, waste recycling, and mitigation of global warming. Smart energy forecasting precision farming and computerized recycling are among the AI-powered solutions being used in India to address significant socioeconomic and ecological issues. Environmental impacts, which include electronic waste excessive energy consumption and harmful effects by rare earth processing, with challenges such as confidentiality of data the digital gap, and limited legal frameworks, pose significant challenges to inclusive AI adoption. The evaluation underlines India’s pressing requirement to implement energy-efficient AI to build green infrastructure, ensure ethical adoption, and strengthens regulatory systems. Artificial Intelligence (AI) has enormous potential to generate long-term and fair prosperity in India if the government, private sector, and academics work together.